Expanding the range of immunopathology in neuromyelitis optica spectrum disorder. (28th July 2016) - Massey, Jennifer; Buckland, Michael E; Barnett, Yael; Sutton, Ian
Abstract : Neuromyelitis optica (NMO) spectrum disorder typically associates with a pathognomonic antibody response directed against aquaporin 4 and a unique immunopathological signature characterised by loss of aquaporin 4 expression. We describe a tumefactive presentation of NMO in which a biopsy specimen demonstrated active demyelination and reactive astrocytes with preserved surface aquaporin 4 immunoreactivity and dystrophic processes. While the astrocytic pathology is more typical of classical multiple sclerosis, a positive NMO-IgG (1:80) and subsequent clinical presentation with an area postrema syndrome is consistent with a diagnosis of NMO spectrum disorder. This report expands the immunopathological features that have been reported in NMO spectrum disorder.